Mycorrization and microbial respiration in soil under passion fruit and jatropha in different water regimes - Souza, Ane Gabriele Vaz; Faria, Layanara Oliveira; Beserra, Gabriela Aparecida; Silva, Gabriela Gomes da; Borges, Larissa Pacheco; Dias, Fernanda Vaz; Matos, Fábio Santos; Santos, Talles Eduardo Borges dos (Revista de Ciências Agroveterinárias, 2022)
Arbuscular mycorrhizal fungi (AMF) and the soil microbial population occupy a prominent role in mitigating the effects caused by water stress in several crops. However, it is necessary to establish parameters on the dynamics of the interaction of these microorganisms with plants under stress conditions. Given the above, this study aimed to evaluate the mycorrhization and microbial respiration of soil cultivated with yellow passion fruit and jatropha seedlings subjected to different water levels. The experiment was carried out in pots in a greenhouse located at the State University of Goiás, Ipameri unit. The design used was completely randomized and analyzed in a 2 x 7 factorial scheme with two plant species (passion fruit and Jatropha curcas) and seven levels of water supply (25%, 50%, 75%, 100%, 125%, 150% and, 175%) in relation to the field capacity (FC) of the soil with five replications, totaling 70 experimental cultivation plots. In addition, soil microbial respiration (MR), number of mycorrhizal spores (SPO) and mycorrhizal colonization (MC) were also evaluated. In terms of MR, the soils responded differently to changes in soil moisture, where the microbiota of the soil with Jatropha curcas was more adapted up to 175% of CC than that of passion fruit. The excess water condition caused a decrease in the SPO of the soil of both crops, but with an effect being more significant in the passion fruit crop, which presented an average of 77.2 spores 50 g-1 of soil. The MC of Jatropha curcas and passion fruit were negatively affected with the increase of soil moisture levels, however, the Jatropha curcas presented an average rate of MC 38.5% higher than the passion fruit. In general, the soil microbiota and the AMF under Jatropha seedlings responded better to water stress.